Supply chain performance measurement: a systematic literature review. Issue 1 (2018) - Guersola, Mariana; Lima, Edson Pinheiro De; Steiner, Maria Teresinha Arns
Through a structured overview of the literature, this paper provides an update and maps the current state of research involving the supply chain performance measurement and management. The results can be used as guidance for future studies. The main research limitations are related to the selected scientific databases, document types and search terms, which can exclude papers that could be pertinent. The findings show that the field of research is still very immature. The reviewed publications are from journals from various areas and researchers from several countries, which shows the breadth of interest in the topic and its importance. Many papers conducted studies to identify the issues involved in supply chain performance measurement and management, and to propose frameworks to solve them, but few studies have been made about effective applications of these proposals. Content analysis covers the most addressed approaches used for the performance measurement and management.